2018
DOI: 10.1007/s00415-018-8863-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced retinal nerve fiber layer (RNFL) thickness in ALS patients: a window to disease progression

Abstract: RNFL thickness in ALS patients is reduced compared to healthy controls. OCT probably could serve as a marker of neurodegeneration and progression of the disease in ALS patients. RNFL thickness is different among the right and left eyes of ALS patients pointing to the fact that asymmetric CNS involvement in ALS is not confined to the motor system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 29 publications
4
55
2
2
Order By: Relevance
“…Differences found between our study and others in OCT measurements [7,[40][41][42][43]45,52] could be due to the early stages of ALS in our patients. The duration of the disease in our patients (10.80 ± 5.5 months, ranging from 1 to 18 months) was shorter than in other published studies, including [45]. Therefore, classifying these patients according to the duration of the disease is important to obtain a better knowledge of the disease.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Differences found between our study and others in OCT measurements [7,[40][41][42][43]45,52] could be due to the early stages of ALS in our patients. The duration of the disease in our patients (10.80 ± 5.5 months, ranging from 1 to 18 months) was shorter than in other published studies, including [45]. Therefore, classifying these patients according to the duration of the disease is important to obtain a better knowledge of the disease.…”
Section: Discussioncontrasting
confidence: 97%
“…However, in our study comparing ALS baseline vs. ALS follow-up, we found significant thinning, both in MT (inferior IMR and OMR areas) and pRNFL (superior and inferior quadrants and in sectors H3, H5, H6, and H12). Other studies using OCT have also demonstrated a thinning of the MT and pRNFL in these patients [40][41][42][43][44][45]. Volpe et al [42] reported that in ALS patients compared with controls, the total macular volume was significantly thinner and 37.5% of ALS patients had a pRNFL average below the first percentile.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations